Virgil's Gaze : Nation and Poetry in the Aeneid - Reed, J. D. (Princeton University Press, 2007)
CONTENTS -- PREFACE -- Introduction -- ONE: Euryalus -- TWO: Turnus -- THREE: Dido -- FOUR: Andromache -- FIVE: Ancient Cities -- SIX: Marcellus -- SEVEN: Aeneas -- BIBLIOGRAPHY -- INDEX OF TEXTS CITED -- A -- B -- C -- D -- E -- F -- H -- J -- K -- L -- M -- N -- O -- P -- Q -- S -- T -- V -- GENERAL INDEX -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- V.